2014
DOI: 10.1590/brag.2014.014
|View full text |Cite
|
Sign up to set email alerts
|

Dimensões lineares da folha e seu uso na determinação do perfil vertical foliar de gladíolo

Abstract: O gladíolo, importante flor de corte, é uma planta herbácea e suas folhas apresentam formato de lança. Os objetivos do trabalho foram determinar um modelo matemático empírico que melhor estima a área da folha do gladíolo a partir de dimensões lineares e aplicar o modelo matemático para determinar o perfil vertical da área das folhas de diferentes posições na planta. Para isso foi realizado um experimento de campo em Santa Maria com quatro cultivares de gladíolo (Peter Pears, Rose Friendship, Jester e Amsterdã)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 11 publications
3
14
0
1
Order By: Relevance
“…1 and 2). Positive correlation was also found for other species as reported by other authors that used equations considering the measurements rib length (Fideles Filho et al, 2010), blade width (Toebe et al, 2011) and/or the product of length and width of the blade (Lucena et al, 2011;Cargnelutti Filho et al, 2012;Bosco et al, 2012, Schwab et al, 2014, which had coefficient of determination above 90% when compared with the actual leaf areas. However, significant correlations are not enough to prove the efficiency of an equation, and it is necessary to determine whether the estimated area is different from the actual area, avoiding estimates that do not represent the true leaf area.…”
Section: Correlation Between Estimated and Actual Leaf Areasupporting
confidence: 80%
“…1 and 2). Positive correlation was also found for other species as reported by other authors that used equations considering the measurements rib length (Fideles Filho et al, 2010), blade width (Toebe et al, 2011) and/or the product of length and width of the blade (Lucena et al, 2011;Cargnelutti Filho et al, 2012;Bosco et al, 2012, Schwab et al, 2014, which had coefficient of determination above 90% when compared with the actual leaf areas. However, significant correlations are not enough to prove the efficiency of an equation, and it is necessary to determine whether the estimated area is different from the actual area, avoiding estimates that do not represent the true leaf area.…”
Section: Correlation Between Estimated and Actual Leaf Areasupporting
confidence: 80%
“…When determining models to calculate the leaf area for fig trees, Souza et al (2014) found that most of the tested mathematical models showed performance "c" indices considered optimum or good. Similar trends were observed in guava and gladioli, where the confidence indices ranged from 0.636 to 0.9371 (Schwab et al, 2014;Silva et al, 2015), which according to Table 1 are classified with performance ranging from "good" to "excellent".…”
Section: Resultssupporting
confidence: 58%
“…A number of methods have been developed to estimate leaf area such as direct or destructive methods, comprising the removal of the leaves, and indirect or nondestructive methods, using mathematical models and leaf linear measurements, which facilitates the work in the field (Sachet et al, 2015;Schwab et al, 2014;Tartaglia et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is indicated that the models of dwarf pigeon pea leaf area estimation in function of the product of the central leaflet length times the width should be preferentially used when the higher accuracy is the objective in relation to the other models that are based only on length or width of the central leaflet, as confirmed by Schwab et al (2014) and Schmildt et al (2015). However, the power model based on the width of the central leaflet can be used, with a small reduction of accuracy, but being less laborious, since only one measured variable is required.…”
Section: Resultsmentioning
confidence: 87%